2014
DOI: 10.1111/evj.12214
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary vaccination regimes for equine influenza: Working towards an evidence‐based regime

Abstract: SummaryReasons for performing study: Vaccination is crucial to the control of equine influenza (EI). The study was conducted in an effort to lay the groundwork for achieving international harmonisation of regulatory requirements based on scientific evidence of performance of different vaccination regimes. Objectives: To evaluate the effectiveness of 3 different primary vaccination regimes: vaccination with the minimal intervals permitted by the racing authorities; vaccination in accordance with the manufacture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
1
20
0
3
Order By: Relevance
“…Vaccination with epidemiologically relevant EIV strains activates the adaptive immune response and provides clinical and virological protection against potential future EIV infection . Strategic vaccination preceding travel and participation in racing events optimises antibody levels during periods of heightened risk of exposure . However, periods of immunological susceptibility and the mixing of naïve horses with vaccinated horses can lead to outbreaks of influenza .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination with epidemiologically relevant EIV strains activates the adaptive immune response and provides clinical and virological protection against potential future EIV infection . Strategic vaccination preceding travel and participation in racing events optimises antibody levels during periods of heightened risk of exposure . However, periods of immunological susceptibility and the mixing of naïve horses with vaccinated horses can lead to outbreaks of influenza .…”
Section: Discussionmentioning
confidence: 99%
“…35 Strategic vaccination preceding travel and participation in racing events optimises antibody levels during periods of heightened risk of exposure. 37 However, periods of immunological susceptibility and the mixing of naïve horses with vaccinated horses can lead to outbreaks of influenza. 38,39 It is preferable to apply mandatory vaccination to all horses that enter a facility irrespective of their activities as seronegative horses are frequently the index case in an outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…This specific vaccine was also shown to induce the highest levels of SRH antibody when compared with other EI vaccines, which could provide an explanation for the lower percentage of poor responder reported after first immunisation [ 79 , 82 ]. The age at the time of first vaccination also seems to influence the response to immunisation [ 151 ], with reduced EI vaccine immunogenicity in weanling and yearlings when compared with older horses [ 151 ]. Antibody titres are usually back to normal levels after the second immunisation.…”
Section: Inefficient or Suboptimal Response Of Horses To Vaccinatimentioning
confidence: 99%
“…, minimum intervals permitted by racing authorities, product labels recommended and longest intervals allowed). Results from this study indicated that overall levels of SRH antibody reached at peaks of immunity were not significantly affected by the nature of the vaccination regimes, however, the duration of the period of susceptibility between V1 and V2, and subsequently V2 and V3 were significantly lengthened when the longest interval scheduled was applied [ 151 ] (study sponsored by the Irish Department of Agriculture). This study confirms that product’s label recommendations should be preferred, when possible.…”
Section: Inefficient or Suboptimal Response Of Horses To Vaccinatimentioning
confidence: 99%
“…Cullinane et al . tested three different primary vaccination schedules as follows: (1) at the minimal intervals stipulated by the racing authorities (i.e. 3 weeks between the first two doses and 5 months before the third dose); (2) according to the vaccine manufacturer's recommendations (i.e.…”
mentioning
confidence: 99%